Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2015)
This progress report presents key conclusions and recommendations from an IEO evaluation of the IMF's response to the global financial and economic crisis and an update of the IEO evaluation of the IMF's approach to capital account liberalization, both issued since October 2014. It also describes ongoing IEO activities.